Unveiling the flavor and quality variations in dried Zanthoxylum bungeanum maxim from China's diverse regions - Xiang Zhu; Di Wu; Lin Zhao; Chenggang Wen; Cao Yong; Qixin Kan (Food Chemistry: X)
Dried Zanthoxylum bungeanum Maxim (DZM) is one of the popular categories in spices and condiments market. The flavor and quality of DZM products determine its value and application scope. This study evaluated the flavor and quality of DZMs from various origins, considering physical, chemical, and safety attributes. Notable variations were observed, with DZMs from Maoxian and Jinyang excelling in aroma, pungency, and appearance. Chromatic analysis distinguished green and red DZMs from Meishan and Hancheng. HPLC results revealed high pungency compound levels in Maoxian and Wudu samples, while GC–MS identified 173 volatile compounds, dominated by linalool and d-limonene. Microbial contamination was minimal in DZMs from Hanyuan and Jiangjin, and the lowest heavy metal levels were in samples from Hanyuan, Hancheng, and Jingyang, indicating superior environmental conditions. The research offered insights into origin and processing influences on DZM, aiding in selection and food safety assurance.